The tenacity of the couple-norm : intimate citizenship regimes in a changing Europe - Roseneil, Sasha, 1966- (UCL Press, 2020)
The Tenacity of the Couple-Norm explores the ongoing strength and insidious grip of couple-normativity across changing landscapes of law, policy and everyday life in four contrasting national contexts: the UK, Bulgaria, Norway and Portugal.By investigating how the couple-norm is lived and experienced, how it has changed over time, and how it varies between places and social groups, this book provides a detailed analysis of changing intimate citizenship regimes in Europe, and makes a major intervention in understandings of the contemporary condition of personal life. The authors develop the feminist concept of 'intimate citizenship' and propose the new concept of 'intimate citizenship regime', offering a study of intimate citizenship regimes as normative systems that have been undergoing profound change in recent decades. Against the backdrop of processes of de-patriarchalization, liberalization, pluralization and homonormalization, the ongoing potency of the couple-norm becomes ever clearer.The authors provide an analysis of how the couple-form is institutionalized, supported and mandated by legal regulations, social policies and everyday practices, and how this serves to shape the intimate life choices and trajectories of those who seem to be living aslant to the conventional heterosexual cohabiting couple-form. Attending also to practices and moments that challenge couple-normativity, both consciously chosen and explicit, as well as circumstantial, subconscious and implicit, The Tenacity of the Couple-Norm makes an important contribution to literatures on citizenship, intimacy, family life, and social change in sociology, social policy, socio-legal studies, gender/sexuality/queer studies and psychosocial studies.